2021
DOI: 10.1063/5.0046033
|View full text |Cite
|
Sign up to set email alerts
|

Application concepts for ultrafast laser-induced skyrmion creation and annihilation

Abstract: Magnetic skyrmions can be created and annihilated in ferromagnetic multilayers using single femtosecond infrared laser pulses above a material-dependent fluence threshold. From the perspective of applications, optical control of skyrmions offers a route to a faster and, potentially, more energy-efficient new class of information-technology devices. Here, we investigate laser-induced skyrmion generation in two different materials, mapping out the dependence of the process on the applied field and the laser flue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
5
30
0
1
Order By: Relevance
“…In line with the modification of the hysteresis behavior for different irradiation doses, we reduced the magnetic field to a value for which spontaneous nucleation of stripe domains remains suppressed but skyrmion nucleation from an external stimulus is possible. 16,27 At the outset, we confirmed that our non-irradiated Pt/CoFeB/MgO multilayer supports skyrmion nucleation. As a reference for the unmodified magnetic film in Fig.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…In line with the modification of the hysteresis behavior for different irradiation doses, we reduced the magnetic field to a value for which spontaneous nucleation of stripe domains remains suppressed but skyrmion nucleation from an external stimulus is possible. 16,27 At the outset, we confirmed that our non-irradiated Pt/CoFeB/MgO multilayer supports skyrmion nucleation. As a reference for the unmodified magnetic film in Fig.…”
supporting
confidence: 58%
“…They finally appear randomly distributed inside the illuminated area of the magnetic film. 23,27 However, a controllable, reproducible and reliable localization of the skyrmion nucleation is often required -both for future applications in data technology 28,29 as well as for fundamental research, e.g., to realize repetitive pump-probe experiments on skyrmion dynamics. 18 Previous attempts to control the localization of skyrmions include structural patterning of the magnetic film with notches 16, 30,31 and discs 11 as well as the introduction of defects 32,33 and nano-pockets 34 to define positions for skyrmion nucleation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their stability and unique topological properties, these textures have sparked ideas for a vast number of technological applications such as (racetrack) memories [7][8][9][10], logical-gates [11,12] and neuromorphic computing [13]. While various control schemes for the manipulation of these textures by means of external magnetic fields [14,15], electrical currents [16][17][18], or optical pulses [3,18,19] are widely established, studies probing their interaction with defects are still highly sought after.…”
Section: Introductionmentioning
confidence: 99%